(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Since coal mining production systems are very complex therefore equipment for repair is more expensive. If the failure of the system, it will cause disturbances such as equipment out of reach, reduced operating time, increased production costs, and reduced equipment performance. Therefore, it is necessary availability of the coal mining industry is considered more than ever. For this purpose, Armored Face Conveyor (AFC) machine failure data gathered over 29 months from Tabas Coal Mine. Descriptive statistics, trends, and the serial correlation test of the data were calculated. Then, the system’s mean and point availability have been simulated. Based on the results the mean availability (all events) and point availability (all events) at 360000 h are 96% and 95%, respectively. The mean time to first failure (MTTFF) of the AFC machine is about 23.61 h. In three metrics ReliaSoft Failure Criticality Index, ReliaSoft Downing Event Criticality Index, and ReliaSoft Downtime Criticality Index electrical equipping have the largest effect whereas the main drive subsystem is the least important. It was found that availability analysis control activities management and improvements in the quality, efficiency, and the product extraction.